Coral reef structured cobalt-doped vanadate oxometalate nanoparticle for a high-performance electrocatalyst in water splitting. (29th August 2022) - Yang, Zhou; Chen, Hanbing; Xiang, Meng; Yu, Chengbin; Hui, Jia; Dong, Shuang
Abstract: Facing the energy crisis in the whole world, it is important to decompose water to obtain high-clean hydrogen energy. However, water splitting by electrocatalysis is suffering from high voltage and poor stability. Herein, we synthesize Co3 V2 O8 coral reef-like nanoparticles in a facile way, showing a low oxygen evolution reaction (OER) overpotential of 318 mV coupled with good stability, which is superior to commercial RuO2 . Besides, the Co3 V2 O8 shows fast kinetics for hydrogen evolution reaction (HER) and small impedance. Furthermore, the Co3 V2 O8 nanoparticles are assembled in symmetric two-electrode system, which has a very low overall water splitting voltage of 1.50 V at 10 mA cm −2, this value surpasses the benchmark RuO2 //Pt/C assembling and most of the other oxometalate-based electrocatalysts. This work provides a novel and facile way of preparing oxometalates nanomaterial electrocatalyst for hydrogen energy. Graphical abstract: Image 1 Highlights: Co3 V2 O8 coral reef-like nanoparticles are firstly synthesized by one-step way. The Co3 V2 O8 nanoparticles show low OER overpotential of 318 mV. The large ECSA of Co3 V2 O8 provides amounts of active sites for water splitting. The Co3 V2 O8 //Co3 V2 O8 system shows the low water splitting voltage of 1.50 V.